"Not like them": New Signers' narrative constructions of the authentic signer. (2019) - Jaeger, Hanna
Abstract: Much of sociolinguistic research aims at exploring various aspects concerning authentic and native speakers. Throughout the literature, both concepts are not only frequently conflated but the corresponding terms oftentimes even used interchangeably. Focusing on emic perspectives of deaf sign language users, and strategically applying a theoretical approach well established in educational and race studies, the research examines how New Signers construct the counter-story of their own status as 'the authentic signer' (TAS) against the backdrop of the master narrative of native signer ideology. The qualitative analysis is based on conversations with 31 deaf signers recorded in the context of 10 focus group, which were conducted in 9 cities throughout Germany. The research demonstrates that participants construct the status of TAS either as inherited or as the outcome of a dynamic process of intentional change. Introducing notions of 'Deaf aristocracy' vs. 'Deaf meritocracy', the paper proposes a significant extension to current conversations about native speaker ideologies by providing empirical evidence that deaf conceptualizations embrace a clear differentiation between authentic and native language users, which therefore must also be upheld in relevant academic discourses. Highlights: Throughout the literature the concepts of authentic speakers and native speakers are used interchangeably. The concept of 'the authentic signer' (TAS) represents a counter-story to the master narrative of the native signer. Deaf signers construct the status of TAS either as inherited ('Deaf aristocracy') or as the outcome of a dynamic process of intentional change ('Deaf meritocracy').